2022
DOI: 10.1186/s12877-021-02731-8
|View full text |Cite|
|
Sign up to set email alerts
|

The influence of primary care quality on nursing home admissions in a multimorbid population with and without dementia in Germany: a retrospective cohort study using health insurance claims data

Abstract: Background Multimorbidity poses a challenge for high quality primary care provision for nursing care-dependent people with (PWD) and without (PWOD) dementia. Evidence on the association of primary care quality of multimorbid PWD and PWOD with the event of a nursing home admission (NHA) is missing. This study aimed to investigate the contribution of individual quality of primary care for chronic diseases in multimorbid care-dependent PWD and PWOD on the duration of ongoing residence at home befo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 54 publications
0
11
0
Order By: Relevance
“…Identifying the common predictors of NHA is considered a key factor in delaying the entry into long-term care services [ 2 ] and in enhancing the development and application of preadmission assessments for managing long-term care utilization among older adults [ 6 ]. Furthermore, identifying predictors of NHA among older adults can increase the understanding of modifiers for functional status, dependency, and utilization of health services for older patients [ 7 , 8 ]. As Gauler et al [ 9 ] reported, NHA can be considered as “less of an endpoint and instead as an important transition where associated factors operate to influence outcomes after admission” [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Identifying the common predictors of NHA is considered a key factor in delaying the entry into long-term care services [ 2 ] and in enhancing the development and application of preadmission assessments for managing long-term care utilization among older adults [ 6 ]. Furthermore, identifying predictors of NHA among older adults can increase the understanding of modifiers for functional status, dependency, and utilization of health services for older patients [ 7 , 8 ]. As Gauler et al [ 9 ] reported, NHA can be considered as “less of an endpoint and instead as an important transition where associated factors operate to influence outcomes after admission” [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…As a result, these studies were at serious risk of confounding. Evidence suggests that PD is associated with multimorbidity [ 40 , 46 ]; multimorbidity is also linked to worse outcomes in older age, including dementia incidence [ 47 ]. We were not able to explore effect of co-morbidities, and future work should account for multimorbidity and seek to make necessary adjustments.…”
Section: Discussionmentioning
confidence: 99%
“…The primary outcome of the underlying project is defined as the institutionalisation of care dependent people. Subsequent analyses [10][11][12][13] focus on determinants from health care and the individuals' care arrangement on the risk of nursing home admission after first onset of care dependency. A selection introduced by record linkage may impair the validity of these analyses.…”
Section: Discussionmentioning
confidence: 99%
“…This article describes the process of linking the two datasets without the presence of a single unique identifier. The aims are to (1) assess the comparability of both datasets, (2) perform and describe the data linkage, (3) assess validity and plausibility of the linkage results with special respect towards the introduction of selection bias into the linked dataset to (4) consequently obtain a dataset allowing to assess institutionalisation of care dependent people in regard to housing and living conditions as well as their received healthcare in subsequent analyses 10–13…”
Section: Introductionmentioning
confidence: 99%